ADEQUACY OF MODELS OF FUNCTIONAL RELIABILITY OF GAS PIPELINE SYSTEM - and (Municipal economy of cities. Series: «Economy science», 2013)
Submitted proof of the adequacy of the analytical method for calculating the functional reliability. The adequacy based on statistical methods that allow direct assessment of a particular indicator of system reliability. With the help of computational experiments that simulates in time and space operation of the system, proved the adequacy of the models considered